Aluminium induced neurodegeneration in rat cerebellum in the presence of ethanol coexposure - Buddhadeb Ghosh; Ravi Kant Sharma; Suman Yadav (Wolters Kluwer Medknow Publications, 2021)
Introduction: Both aluminium and ethanol are pro-oxidants and neurotoxic. Moderately intake of alcohol may favor the body in coronary heart disease and diabetes mellitus etc. Being cheaper aluminium and increasing consumption of alcohol in India mixed with each other and may induce neurotoxicity. The present study was planned to identify the level of aluminium induced neurodegeneration in presence of ethanol coexposure in the cerebellum. Materials and Methods: An experimental study was carried out at Dr. RP Government Medical College, Kangra, and Government Medical College, Amritsar, India after due approval from the Institute Animal Ethics Committee. Thirty-two Wistar rats were divided into one vehicle control and three experimental groups. Group I received the normal saline water as the vehicle control group. Group II received aluminium chloride 4.2 mg/kg body weight as the experimental group. Group III received ethanol 1 g/kg body weight as the experimental group. Group IV received both aluminium chloride 4.2 mg/kg body weight and ethanol 1 g/kg body weight as the experimental group. After 3 months of treatment, cerebellum was processed for histopathological observation under the microscope. Results: Experimental group treated with aluminium and ethanol separately showed reduction in the number of Purkinje cells, without a prominent nucleolus and well-defined nuclear membrane. Eosinophilic swelling adjacent to Purkinje cell bodies observed. The effects of combined administration of aluminium ethanol treated groups showed with acute neurodegeneration of Purkinje cell layer and granular layer. Pyknosis and neurofibrillary tangle seen in Purkinje cells. Conclusions: It has been suggested that the ethanol-induced the effects of aluminium on the cerebellum and plays a significant role in neurotoxicity.